EFNS guidelines on neuropathic pain assessment: revised 2009 - Cruccu, Giorgio; Sommer, C.; Anand, P.; Attal, N.; Baron, R.; Garcia-Larrea, L.; Haanpaa, M.; Jensen, T. S.; Serra, J.; Treede, Rolf-Detlef (European journal of neurology, 2010)
BACKGROUND AND PURPOSE: We have revised the previous EFNS guidelines on neuropathic pain (NP) assessment, which aimed to provide recommendations for the diagnostic process, screening tools and questionnaires, quantitative sensory testing (QST), microneurography, pain-related reflexes and evoked potentials, functional neuroimaging and skin biopsy. - METHODS: We have checked and rated the literature published in the period 2004-2009, according to the EFNS method of classification for diagnostic procedures. - RESULTS: Most of the previous recommendations were reinforced by the new studies. The main revisions relate to: (i) the new definition of NP and a diagnostic grading system; (ii) several new validated clinical screening tools that identify NP components, and questionnaires which assess the different types of NP; (iii) recent high-quality studies on laser-evoked potentials (LEPs) and skin biopsy. - CONCLUSIONS: History and bedside examination are still fundamental to a correct diagnosis, whilst screening tools and questionnaires are useful in indicating probable NP; QST is also useful for indicating the latter, and to assess provoked pains and treatment response. Amongst laboratory tests, LEPs are the best tool for assessing Adelta pathway dysfunction, and skin biopsy for assessing neuropathies with distal loss of unmyelinated nerve fibres.
Gesehen am 19.07.2023